The Influence of Student Teams Achievement Divisions Assurance Approach, Rellevance, Interest, Assessment, Satisfaction towards Improvement Mathematical Understanding - Aeni, Nurul; Habibi, Aulia Farkhan (Faculty of Tarbiya and Teacher Trainning, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
The ability to understand mathematics is a fundamental aspect that must be possessed by students every student, because having this ability can help students to master other mathematical concepts. However, the fact is that many students have comprehension abilities low mathematics. One of the factors that causes low mathematical understanding abilities students is the application of a learning model that does not provide students with opportunities to play an active role during learning. This has an impact on students' difficulties in learning and understand mathematical material. So, a solution is needed to overcome this, one of which is is to apply the STAD type cooperative learning model with the ARIAS approach. This research aims to determine the mathematical understanding abilities of class VIII students function material by applying the STAD type cooperative learning model with approach ARIAS. The research population was all students of class VIII MTs Ma'arif NU 1 Sokaraja, with Using convenience sampling techniques, the research sample was obtained, namely class VIII A students as the experimental class and class VIII B students as the control class, totaling 53 students. Type The research used is quantitative research with experimental and design methods pre-test and post-test control group. Data collection techniques were carried out using the observation method and tests in the form of pre-test and post-test. After the data is collected, the data is analyzed using t test for two independent samples, with prerequisite tests in the form of a normality test and a homogeneity test. Based on analysis using the t test for two independent samples obtained a significance value in the post-test data of 0.000 > 0.05 which indicates there is a significant difference between the average value of the experimental class and control class. Thus, it can be concluded that the STAD type cooperative learning model The ARIAS approach has an effect on increasing mathematical understanding abilities class VIII students. Keywords: Mathematical Understanding Ability; ARIAS Models; STAD model